The relationship between Iranian EFL learners’ self-perceived knowledge and loyalty to Iranian culture and their attitudes toward cultural differences in their first year and last year of studying at university / Seyed Hassan Talebi and Habibollah Halimi Jelodar - Talebi, Seyed Hassan; Jelodar, Habibollah Halimi (ACRULeT, Faculty of Education & UiTM Press, 2013)
This study used mixed method research to fi nd out about Iranian EFL learners self-perceived knowledge and loyalty to their Iranian and Islamic culture and their attitude toward cultural differences in their fi rst and last year of studying at university. 40 senior students, majoring in English Language and Literature were asked to rate their self-perceived knowledge of and loyalty to their own Iranian and Islamic culture and then answer the questionnaire about attitudes toward cultural differences. They were also interviewed about this. The analysis of data showed fi rst, there was a positive relationship between Iranian EFL students’ knowledge of and loyalty to their own culture. Second, no relationship was found between students’ attitudes toward cultural differences and their knowledge of and loyalty to their own culture. Third, it was found that there was a signifi cant improvement in the degree of ethnorelativism from fi rst to last year of studying at university. It is concluded that students can have an ethnorelative attitude toward cultural differences and at the same time, be loyal to their own culture.